Target amplicon exome-sequencing identifies promising diagnosis and prognostic markers involved in RTK-RAS and PI3K-AKT signaling as central oncopathways in primary central nervous system lymphoma - Takashima, Yasuo (Oncotarget, 2018)
Exome-sequencing for somatic mutation detection and copy number variation analysis are effective and valid methods for evaluating human cancers in current molecular medicine. We conducted target amplicon exome-sequencing analyses using PCR target enrichment and next-generation sequencing on Ion Proton semiconductor sequencers. Twenty-seven primary central nervous system lymphoma (PCNSL) specimens and their corresponding noncancerous tissues were used for multiplex PCR amplification to obtain targeted coverages of the entire coding regions of 409 cancer-related genes. The average of the total numbers of somatic mutations including single-nucleotide variations and insertion/deletion mutations in each specimen was 13.3. Of these, the average of the ratios of nonsynonymous substitutions in each specimen was 74.8%. The most frequent mutations in 27 specimens were in PIM1, MYD88, CD79B, DST, IRF4, ERBB3, MYH11, DCC, and KMT2D. Furthermore, somatic mutations of MYH11 were related to poor prognoses in PCNSL patients. Copy number variations were also duplicated and/or deleted from deep-sequencing in segmental genomic islands. In addition to these prognostic marker candidates, analysis of RTK-RAS-MAPK signaling and the PTEN-PI3K-AKT proapoptotic pathway showed that somatic activations and aberrations, respectively, may be involved in a promising central oncopathway harboring mTOR, c-Myc, FOXO1, and p53. This study provides a foundation for molecular targeted therapies based on genome diagnostics and prognosis in PCNSL.